PENGARUH CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN TAMBANG BATU BARA TERHADAP KESEJAHTERAAN MASYARAKAT KAMPUNG PEGAT BUKUR - Nelly, Nelly; Purwanto, Sayugo Adi; Suriansyah, Suriansyah (STIE Muhammadiyah Tanjung Redeb, 2017)
The prosperity of human society is an ultimate thing that should be prioritised, the establishment of the company in the midst of society through corporate social responsibility program which is consistent will  make the existence of the community become better accordance with the results obtained where there is a positive result (the same aim) to the variable of community prosperity of  Pegat Bukur Village with a coefficient of 0.045, but is not have a significant influence on living standards of Kampat Pegat Bukur community it is seen from the results of the 0.4% coefficient test against the Community prosperity at  Pegat Bukur village, while the rest of 99.6%. Affected by other variables.